(untitled) (Simbiótica. Revista Eletrônica, 2024)
The present research aims to understand what would have led a social agent who did not graduate in Social Sciences to act as a sociologist, namely: creating didactic works, working in the organization of works, contributing to the creation of Social Sciences courses. The analysis considers two interdependent “dimensions”: social structure, social dispositions and agency. We will consider that Azevedo’s sociological practical sense is the result of the disposition incorporated in his professional socializing experiences within the social fields in which he was immersed, as well as the political and economic context favorable to his action. Understanding the social structure and the symbolic capitals disputed will provide us with elements to develop how a sociologist was produced, without having graduated in Social Sciences or Sociology. We seek to investigate the practices of the aforementioned author, the places they were inserted, the relationships they maintained to understand social incorporations, we will carry out our study from theoretical-methodological perspectives based on Pierre Bourdieu, bringing us closer to a dispositionalist Sociology.